IMPLEMENTASI UU NO. 16 TAHUN 2019 PERUBAHAN ATAS UU NO. 1 TAHUN 1974 TENTANG PERKAWINAN SEBAGAI UPAYA PERLINDUNGAN HUKUM TERHADAP PEREMPUAN - Huda, Zainul; Shoelsap, Mudzakkir (USRATUNA: Jurnal Hukum Keluarga Islam, 2022)
Law No. 16 of 2019 is a law that changes one of the articles in Law No. 1 of 1974 concerning Marriage, namely Article 7 which relates to the age limit for marriage. The essence of the change is changing the minimum age limit for marriage for women from 16 years to 19 years. The Office of Religious Affairs as the executor of the amendment to the law must of course implement it effectively, especially the KUA Kec. Diwek Kab. Jombang. Not to mention, besides having to implement it, KUA Kec. Diwek Kab. Jombang must also try to provide legal protection, especially for women with all aspects that include it because of the enactment of the law. To find a way out of these problems, the researcher uses a field research type with a qualitative approach, where the researcher acts as a full observer by collecting interview data and related archives and analyzing using descriptive analysis methods. The discussion of the data obtained from the research findings can be revealed that: (1) The implementation of Law No. 16 of 2019 has been implemented effectively through outreach activities carried out by the Head of KUA, extension workers and also assistants to the penghulu. (2) KUA's efforts in providing legal protection, especially for women, have been carried out to the maximum through several suggestions and also solutions for those who are going to marry, especially those who are underage.